1983
DOI: 10.1177/0022002183014003004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Schooling on Conservation Skills

Abstract: Previous studies have tried to explain or predict conservation skills in terms of "schooled" or "unschooled." In this study, an intervention in some schools in the Ciskei, South Africa, is described and its effect on conservation skills is investigated. The results suggest that the acquisition of conservation skills may depend more on factors such as physical and mental interaction with the environment, and the type of reasoning to which a child is exposed, than on schooled and unschooled categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Using the results obtained from a Science Reasoning Task (Adey, 1976) applied to 602 Ciskei pupils (Macdonald, 1980a), it was found that many of the topics in the syllabus were beyond the reasoning ability of pupils. Rogan and Macdonald (1983) showed that the intervention of SEP into school science in the Ciskei improved the conservation skills of pupils.…”
Section: Observations Of Science Teaching Elsewherementioning
confidence: 99%
“…Using the results obtained from a Science Reasoning Task (Adey, 1976) applied to 602 Ciskei pupils (Macdonald, 1980a), it was found that many of the topics in the syllabus were beyond the reasoning ability of pupils. Rogan and Macdonald (1983) showed that the intervention of SEP into school science in the Ciskei improved the conservation skills of pupils.…”
Section: Observations Of Science Teaching Elsewherementioning
confidence: 99%
“…In a study of conservation of continuous quantity and number among Yoruba and Oje children in Nigeria, Lloyd (1971) reported that Oje girls' performance was significantly inferior to that of Oje boys, irrespective of the familiarity of the test material. Rogan and Macdonald (1983), working with Xhosa children of Ciskei, South Africa, attempted to address the question of whether differences in teaching patterns and learning experiences could affect specific conservation skills. Using the Science Education Project (SEP), the selection was taken from nine classrooms in six 'project schools and nine classrooms in five control schools.…”
Section: Introductionmentioning
confidence: 99%